Triboelectric charging behaviors and photoinduced enhancement of alkaline earth ions doped inorganic perovskite triboelectric nanogenerators. (November 2020) - Wang, Yudi; Yang, Xiya; Yu, Xueping; Duan, Jialong; Yang, Qianming; Duan, Yanyan; Tang, Qunwei
Abstract: The in-depth understanding on the electrification behavior of dielectric materials is a prerequisite to improve their surface triboelectric charge density in triboelectric nanogenerators (TENGs). Herein, triboelectric charging affinities and polarities of all-inorganic cesium lead tri-bromine (CsPbBr3 ) and alkaline earth ions doped CsPb1- x M x Br3 (M = Mg 2+, Ca 2+, Sr 2+, Ba 2+, x  = 0–1) perovskites are systematically investigated by assembling into vertical contact-separation TENGs. An enriched triboelectric series supplemented with pristine CsPbBr3 and CsPb1- x M x Br3 perovskites with quantified triboelectric charging polarity is presented through analyzing the electrical output performances, figure-of-merits (FOM), dielectric property, work function, bond energy and electron binding energy. Systematical analyses of three different configurations of dielectric/perovskite TENG, carbon/perovskite TENG and perovskite solar cell are compared in dark and under illumination. It is found that the photoinduced charges play significant role in enhancing the triboelectrification charges and altering charging polarity of perovskite. Our work supplements inorganic perovskites to triboelectric series and provides new insights on inorganic perovskite in the foundation of tribo-photovoltaic theory and triboelectric devices. Graphical abstract: Alkaline earth ions doped CsPb1- x M x Br3 perovskites are systematically investigated regarding on their triboelectrification behaviors and charging polarities for an enriched triboelectric series, current output is significantly enhanced through coupling of triboelectric and photovoltaic effects based on CsPbBr3 perovskite TENG. Image 1 Highlights: Impacts of alkaline earth ions doping contents of CsPb1- x M x Br3 perovskites on output performances are investigated. Supplemented triboelectric series comprising CsPb1- x M x Br3 perovskites with quantified charging polarity is delivered. Reversed voltage and highly enhanced current signal of CsPbBr3 TENG are obtained by tribo-photovoltaic effect. Reversed voltage and highly enhanced current signal of CsPbBr3 TENG are obtained by tribo-photovoltaic effect.